Auf segelbeflügelten Schiffen das Meer befahren : Das Erlebnis der Schiffsreise im späten Hellenismus und in der Römischen Kaiserzeit. In Zusammenarbeit mit Jens Börstinghaus. / Mario Baumann, Susanne Froehlich, in Zusammenarbeit mit Jens Börstinghaus - Baumann, Mario (Philippika / Altertumskundliche Abhandlungen., 2018)
navibus velivolis magnum mare saepe cucurri / "I have often sailed the great sea on sail-winged ships" - that is what an imperial inscription from Brundisium reads. In ancient times, seafaring was a comparatively comfortable, fast and inexpensive way of getting around, which was particularly suitable for this To open up wide geographical areas. The tradition of ancient texts that deal with journeys by ship in a wide variety of contexts is correspondingly rich. The anthology is dedicated to these texts in ancient historical and ancient philological approaches and presents the experience of the sea voyage as a cultural phenomenon The timeframe ranges from texts from the 1st century BC to depictions from the late imperial era.Methodically, the aim is twofold: on the one hand, the 18 contributions analyze the experience horizons of ancient travelers, on the other hand they examine them the way of lit erar representation of sea voyages and ask about the function of the textual design.